Automotive radiators: An experimental analysis of hybrid nanocoolant - Hizanorhuda, Zurghiba; Kumaran, Kadirgama; Muhamad, Mat Noor; Rosli, Abu Bakar; Semin, S. (EDP Sciences, 2024)
A hybrid nanocoolant is a novel type of heat transfer enhancement medium that has the potential to enhance the performance of automotive radiators by improving heat transfer efficiency and heat dissipation. The focus of the present work was to investigate the effect of different hybrid nanocoolant mixing ratios on Reynolds number, Nusselt number, Friction factor, heat transfer coefficient and convective heat transfer on heat transfer performance. Single and its hybrid nanocoolant were tested through a commercial-sized automotive radiator and a scaled-down automotive radiator to determine its laminar convective heat transfer. The nanocoolants are prepared with a fixed volume fraction of 0.01 vol% and for hybrid nanocoolants, different ratios of CNC and CuO nanoparticles are formulated. The studies utilised flow rates of 0.75, 1.00, and 1.25 LPM with a radiator inlet liquid temperature of 80°C. The experimental results show that the Reynolds number, Nusselt Number, heat transfer coefficient and convective heat transfer are proportionally related to the volumetric flow rate, while the friction factor decreases when there is an increase in the flow rate. A scale-down radiator with a low-volume concentration of hybrid nanofluids able to improve the heat transfer efficiency by 92.43% compared to conventional fluids in a commercial-sized car radiator.